2004
DOI: 10.1089/109493104322820101
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Social Skills, and Adjustment

Abstract: The present study investigated the extent to which inter-personal skills, personality, and emotional intelligence (EI) were related to the extent of usage of the Internet, as measured with the Internet Addiction Scale, on a sample of undergraduates. EI was assessed by performance measures derived from the identification and labeling of emotions as shown in pictures of facial expressions, and as interpreted from descriptions of social episodes. Use of the Internet was related to loneliness and adherence to idio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
171
4
23

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(210 citation statements)
references
References 43 publications
10
171
4
23
Order By: Relevance
“…This findings is consistent with the results of Cao et al [12], Yen et al [18], Young et al [24], Jang et al [19], Ko et al [25], Engelberg and Suberg [26], Yenjyko et al [27], Yun et al [28], Alavi et al [6], and Nastizaee [5] who indicated that the level of anxiety of the Internet addicted students was more than that of other students. An explanation is that the cause of the relationship between anxiety and Internet addiction is not clear yet.…”
Section: Discussionsupporting
confidence: 90%
“…This findings is consistent with the results of Cao et al [12], Yen et al [18], Young et al [24], Jang et al [19], Ko et al [25], Engelberg and Suberg [26], Yenjyko et al [27], Yun et al [28], Alavi et al [6], and Nastizaee [5] who indicated that the level of anxiety of the Internet addicted students was more than that of other students. An explanation is that the cause of the relationship between anxiety and Internet addiction is not clear yet.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, having the opportunity of maintaining the communication on the internet environment not only spending time within the social life could positively affect the social support individuals would perceive. Although it was reported in the previous researches that social and psychological well-being levels of the individuals who spent less time on the social networking websites were higher (Moore and McElroy, 2012;Nie, 2001;Nie and Erbring, 2000;Turkle, 1996;Stoll, 1995),it should not be forgotten that overuse of such communication instruments could drive individuals to loneliness (Engelberg and Sjoberg, 2004), and as the level of social support individuals perceived from their families decreased, individuals' level of internet addiction could increase (Günüç, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…Individuals have started to commonly use the opportunities internet has recently provided for reaching to information, making shares, socializing or establishing new friendships. However, individuals have been noticed to have problems such as experiencing increase at feeling anger, communication problems and feeling loneliness whereas they have been expected to experience the positive improvements provided by the internet (Whang, Lee and Chang, 2003;Tsai and Lin, 2003;Engelberg and Sjoberg, 2004;Yang and Tung, 2007;Karaca, 2007;Ata, Akpınar and Kelleci, 2011;Çelik, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations